Evaluation of a novel reprocessed bCPAP system on sepsis rates among preterm neonates with respiratory distress: a randomized controlled trial - Badin, Sarah; Roodaki, Navid; Garcia, Daisy Evangeline C.; Abila-Cariaga, Rochelle; Burke, Thomas F. (Frontiers in Pediatrics, 2025)
IntroductionBubble CPAP (bCPAP) is highly effective in the treatment of respiratory distress syndrome of prematurity and other causes of newborn respiratory insufficiency. To overcome barriers to bCPAP access a novel system was developed that is designed to be cleaned, disinfected, and reused. This study evaluated whether use of reprocessed bCPAP systems increases the rate of sepsis in neonates.MethodsA post hoc analysis of a single-center randomized controlled trial (registration no. NCT06082674) was conducted that compared mechanical ventilator driven CPAP devices (MV-CPAP) with single-use circuits to reusable bCPAP systems that were cleaned and disinfected after each use. The primary outcome was a composite of treatment escalation or death.ResultsSeventy-five neonates were randomized to the two CPAP treatment arms. No significant differences in death (5 vs. 4), escalation of care (10 vs. 9), and the composite outcome (OR = 0.84; 95% CI: 0.30–2.35, p = 0.743) were detected in the MV-CPAP and bCPAP groups respectively. There were no clinically significant differences in any of the secondary outcomes.DiscussionUse of a reprocessed bCPAP system designed to increase global access to CPAP did not increase rates of neonatal sepsis.Clinical Trial RegistrationClinicalTrials.gov, identifier, (NCT06082674).